INTERNALIZATION OF MULTICULTURAL VALUES OF ISLAMIC RELIGIOUS EDUCATION IN FOSTERING STUDENT TOLERANCE CHARACTER IN SMK NEGERI 3 SINGKAWANG CITY - Putra, Purniadi; Abdul Hafiz (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research aims to explore the internalization of multicultural values in Islamic Religious Education in fostering students' tolerance character. This research uses a qualitative approach with observation, interview and documentation methods. Primary data sources; Islamic Education Teacher, Principal, Waka Kesiswaan, BK Teacher and Students of SMK Negeri 3 Singkawang. The analysis technique used; data reduction, data presentation and conclusion drawing/verification to identify the value transformation process applied. The results showed that the active involvement of students in joint religious activities, initiatives such as Joint Infaq every Friday, and cultural exchange activities has encouraged the creation of mutual respect without religious or ethnic discrimination. In addition, the zero tolerance policy against discrimination fosters an inclusive and harmonious environment at school. This internalization process can also be seen from the students' ability to resolve conflicts effectively and establish constructive cooperation. The implication of this research emphasizes the importance of the teacher's role in transforming multicultural values to strengthen the character of tolerance, which in turn can contribute positively to building social harmony in a plural society.